Photosensitive glass-ceramics and method for preparing the same, chemically strengthened photosensitive glass-ceramics

CN123003149APending Publication Date: 2026-10-30CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611401492.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

现有光敏玻璃在性能对比度以及可加工性等方面存在一定的局限性,难以满足一些对材料强度要求较高的应用场景

Benefits of technology

[0031]本申请提供了一种光敏微晶玻璃、化学强化光敏微晶玻璃及其制备方法,基础玻璃组分包括:SiO2:65wt%~74wt%、Al2O3:5wt%~9wt%、Li2O:8wt%~12wt%、Na2O:1wt%~3wt%、K2O:2wt%~4wt%、ZrO2:4wt%~7wt%、CeO2:0.05wt%~0.32wt%、Sb2O3:0.3wt%~0.7wt%、SnO2:<0.32wt%、X:0.2 wt %~0.80 wt %,其中,X为Ag的氧化物;所述光敏微晶玻璃包括曝光区域与非曝光区域;所述曝光区域和所述非曝光区域高度差为Δd1,30nm≤Δd1≤62nm。本申请通过对基础玻璃的成分进行设计,能够减小曝光区域和非曝光区域的高度差,控制适宜的离子交换速度、进而控制强化过程的质量相对损失率较小,能够实现化学强化光敏微晶玻璃具有高抗冲击性能与高抗压强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003149A_ABST
    Figure CN123003149A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of glass materials, and provides a photosensitive microcrystalline glass, a preparation method thereof and a chemically strengthened photosensitive microcrystalline glass. The basic glass component comprises SiO2: 65-74 wt%, Al2O3: 5-9 wt%, Li2O: 8-12 wt%, Na2O: 1-3 wt%, K2O: 2-4 wt%, ZrO2: 4-7 wt%, CeO2: 0.05-0.32 wt%, Sb2O3: 0.3-0.7 wt%, SnO2: 0-0.32 wt% and X: 0.2-0.80 wt%, wherein X is an oxide of Ag; the photosensitive microcrystalline glass comprises an exposed area and a non-exposed area; the height difference between the exposed area and the non-exposed area is Delta d1, and 30 nm <= Delta d1 <= 62 nm. Through the design of the components of the basic glass, the crystallinity difference and the height difference between the exposed area and the non-exposed area can be reduced, and then the chemically strengthened photosensitive microcrystalline glass has high impact resistance and high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application filed on April 15, 2026, with application number 202610499908.4 and invention title "Photosensitive microcrystalline glass and its preparation method, chemically strengthened photosensitive microcrystalline glass". Technical Field

[0002] This application relates to the field of glass materials technology, and in particular to a photosensitive microcrystalline glass and its preparation method, and a chemically strengthened photosensitive microcrystalline glass. Background Technology

[0003] By employing ultraviolet exposure and heat treatment processes, opaque regions with significant light-blocking properties can be formed within photosensitive microcrystalline glass. The light transmittance of these regions is significantly lower than that of the matrix glass, and their light-blocking performance stems from enhanced light scattering and increased interface reflection caused by the formation of the microcrystalline structure. Existing photosensitive glass has limitations in terms of performance contrast and processability, making it difficult to meet the requirements of some applications with high material strength requirements. For example, the difference in glass properties between the exposed and non-exposed areas leads to inconsistent relative glass loss rates during the strengthening process, creating a height difference between the exposed and non-exposed areas, which makes it difficult to meet the drop ball requirements of chemically strengthened microcrystalline glass. Furthermore, during chemical tempering, the inconsistent shrinkage between the exposed and non-exposed areas can easily lead to cracks and edge chipping, affecting product quality and production efficiency.

[0004] Therefore, developing a photosensitive microcrystalline glass with high impact resistance and high compressive strength, as well as its preparation method and application, is of great practical significance. Summary of the Invention

[0005] The purpose of this application is to provide a photosensitive microcrystalline glass, a chemically strengthened photosensitive microcrystalline glass, and a method for preparing the same, which can reduce the difference in crystallinity and height between the exposed and unexposed areas, thereby enabling the chemically strengthened photosensitive microcrystalline glass to possess high impact resistance and high compressive strength. The specific technical solution is as follows:

[0006] The first aspect of this application provides a photosensitive microcrystalline glass, the base glass composition of which includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: 0wt%~0.32wt%, X: 0.2wt%~0.80wt%, wherein X is an oxide of Ag; the photosensitive microcrystalline glass includes an exposed region and a non-exposed region; the height difference between the exposed region and the non-exposed region is Δd1, where 30nm≤Δd1≤62nm.

[0007] In one embodiment of this application, Y is (SiO2+Al2O3) / (ZrO2+K2O), and 7≤Y≤11.

[0008] In one embodiment of this application, Z is SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O), and 6≤Z≤9.

[0009] In one embodiment of this application, the crystallinity of the exposed area is 1.7%-10%, preferably 1.7%-5.8%; the crystallinity of the unexposed area is 0.4%-3%, preferably 0.4%-2.74%.

[0010] In one embodiment of this application, the absolute value of the difference in crystallinity between the exposed area and the unexposed area is 0-6%.

[0011] The second aspect of this application provides a chemically strengthened photosensitive microcrystalline glass, the base glass composition of which includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: <0.3 2wt%, X: 0.2%~0.80%, wherein X is an oxide of Ag, the chemically strengthened photosensitive glass-ceramic includes an exposed region and a non-exposed region, the height difference between the exposed region and the non-exposed region is Δd2, 40nm≤Δd2≤180nm; the CS of the non-exposed region is 200MPa-350MPa, preferably 280MPa-320MPa; the CS_50 of the non-exposed region is 65MPa-180MPa, preferably 88MPa-110MPa.

[0012] In one embodiment of this application, Y is (SiO2+Al2O3) / (ZrO2+K2O), and 7≤Y≤11.

[0013] In one embodiment of this application, Z is SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O), and 6≤Z≤9.

[0014] In one embodiment of this application, the falling ball impact energy of the chemically strengthened photosensitive microcrystalline glass is 0.30J-0.48J.

[0015] In one embodiment of this application, the static compressive strength of the chemically strengthened photosensitive microcrystalline glass is 300N-400N.

[0016] In one embodiment of this application, the drop height of the chemically strengthened photosensitive microcrystalline glass is 50cm-75cm.

[0017] The third aspect of this application provides a method for preparing the photosensitive microcrystalline glass provided in the first aspect of this application, comprising the following steps:

[0018] (1) Prepare raw materials according to the composition, mix, melt, shape and anneal the raw materials to obtain base glass;

[0019] (2) The base glass is processed to obtain a glass substrate sheet;

[0020] (3) Divide the glass substrate sheet into a first region and a second region, perform masking treatment on the first region, and do not perform masking treatment on the second region to obtain the masked substrate glass;

[0021] (4) The masked substrate glass is subjected to radiation treatment to obtain irradiated substrate glass; the first region of the irradiated substrate glass is a non-exposed region, and the second region of the irradiated substrate glass is an exposed region.

[0022] (5) The irradiated substrate glass is heat-treated to obtain photosensitive microcrystalline glass.

[0023] In one embodiment of this application, the heat treatment includes nucleation treatment and crystallization treatment; the temperature of the nucleation treatment is 450℃-500℃, the time of the nucleation treatment is 210min-250min, the heating rate of the crystallization treatment is 1℃ / min-10℃ / min, the temperature of the crystallization treatment is 595℃-610℃, and the time of the crystallization treatment is 30min-47min.

[0024] In one embodiment of this application, the masking process includes masking using double-sided ink printing or double-sided masking, wherein the first region has an optical density >5 at a wavelength of 380nm-780nm after the masking process.

[0025] In one embodiment of this application, the radiation treatment includes: ultraviolet light irradiation for 5-10 minutes, wherein the wavelength of the ultraviolet light irradiation is 300nm-320nm, and the intensity of the ultraviolet light irradiation is 89mw / cm². 2 -260mw / cm 2 .

[0026] The fourth aspect of this application provides a method for preparing chemically strengthened photosensitive microcrystalline glass, comprising subjecting the photosensitive microcrystalline glass described in the first aspect to a two-step chemical strengthening treatment, wherein the two-step chemical strengthening treatment includes:

[0027] First step chemical strengthening: The photosensitive microcrystalline glass is placed in a salt bath in a mixed nitrate solution containing 0wt%-40wt% KNO3, 60wt%-100wt% NaNO3 and 0wt%-0.03wt% LiNO3. The temperature of the first step chemical strengthening is 360℃-400℃ and the time of the first step chemical strengthening is 20min-50min.

[0028] The second step of chemical strengthening: The photosensitive microcrystalline glass after the first step of chemical strengthening is placed in a salt bath in a mixed nitrate containing 0wt%-10wt% NaNO3 and 90wt%-100wt% KNO3. The temperature of the second step of chemical strengthening is 365℃-405℃, and the time of the second step of chemical strengthening is 10min-25min.

[0029] The fifth aspect of this application provides the application of the photosensitive microcrystalline glass described in the first aspect or the chemically strengthened photosensitive microcrystalline glass described in the second aspect in smart wearable devices, mobile terminals, camera modules or vehicle components.

[0030] The beneficial effects of this application are:

[0031] This application provides a photosensitive microcrystalline glass, a chemically strengthened photosensitive microcrystalline glass, and a method for preparing the same. The basic glass composition includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: <0.32wt%, X: 0.2wt%~0.80wt%, where X is an oxide of Ag. The photosensitive microcrystalline glass includes an exposed region and a non-exposed region. The height difference between the exposed region and the non-exposed region is Δd1, where 30nm≤Δd1≤62nm. This application, by designing the composition of the base glass, can reduce the height difference between the exposed and unexposed areas, control the appropriate ion exchange rate, and thus control the relative loss rate of the strengthening process to be small, thereby enabling chemically strengthened photosensitive microcrystalline glass to have high impact resistance and high compressive strength.

[0032] Of course, implementing any product or method of this application does not necessarily require achieving all of the advantages described above at the same time. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.

[0034] Figure 1 These are XRD patterns of the exposed and unexposed areas in Embodiment 1 of this application;

[0035] Figure 2 The XRD patterns of the exposed and unexposed areas in Comparative Example 9 of this application are shown below.

[0036] Figure 3a This is a height difference diagram of the exposed and unexposed areas before enhancement in Embodiment 10 of this application - a white light interference color fringe diagram;

[0037] Figure 3b This is a diagram showing the height difference between the exposed and unexposed areas before enhancement, along with a white light interference curve, in Embodiment 10 of this application.

[0038] Figure 4a This is a height difference diagram of the exposed and unexposed areas after enhancement in Embodiment 10 of this application - a white light interference color fringe diagram;

[0039] Figure 4bThis is a height difference diagram of the exposed and unexposed areas after enhancement, presented as a white light interference curve in Embodiment 10 of this application.

[0040] Figure 5a This is a height difference diagram of the exposed and unexposed areas before enhancement in Comparative Example 9 of this application - a white light interference color fringe diagram;

[0041] Figure 5b This is a diagram showing the height difference between the exposed and unexposed areas before enhancement, along with a white light interference curve, in Comparative Example 9 of this application.

[0042] Figure 6a This is a height difference diagram of the exposed and unexposed areas after enhancement in Comparative Example 9 of this application - a white light interference color fringe diagram;

[0043] Figure 6b This is a white light interference curve showing the height difference between the exposed and unexposed areas in Comparative Example 9 of this application after enhancement. Detailed Implementation

[0044] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.

[0045] The first aspect of this application provides a photosensitive microcrystalline glass, the base glass composition of which includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: 0wt%~0.32wt%, X: 0.2wt%~0.80wt%, wherein X is an oxide of Ag; the photosensitive microcrystalline glass includes an exposed region and a non-exposed region; the height difference between the exposed region and the non-exposed region is Δd1, where 30nm≤Δd1≤62nm. The inventors discovered that due to differences in glass properties, such as composition and crystallinity, between the exposed and unexposed areas—the exposed area containing a large amount of lithium metasilicate and Ag nanocrystals, while the unexposed area contains a small amount of lithium metasilicate crystalline phase—there is a difference in hardness between the exposed and unexposed areas, forming a step (height difference) before strengthening. The stress concentration caused by this height difference can lead to glass breakage at unexpected locations (such as protrusions or depressions), resulting in breakage during testing due to the impact of a falling ball under non-uniform stress. This application addresses this by designing the composition of the base glass to reduce the height difference between the exposed and unexposed areas.

[0046] In one embodiment of this application, Y is (SiO2+Al2O3) / (ZrO2+K2O), where 7≤Y≤11. SiO2 is the core forming body of the glass network, determining the basic stability of the framework; Al2O3, as a network intermediate, can complete the network structure through [AlO4] tetrahedra, effectively suppressing spontaneous crystallization in the non-exposed area and avoiding devitrification in the transparent area. ZrO2 is a grain refiner and crystallization promoter, regulating the precipitation and grain size of the lithium metasilicate phase in the exposed area; K2O is a flux and ion exchange regulating component, directly affecting the crystal growth rate and molten salt ion diffusion efficiency. One of the core defects of the current prior art is that the ion exchange rate is inconsistent between the exposed and non-exposed areas due to the different glass properties, resulting in uneven stress distribution after strengthening and easy cracking and edge breakage. In the formula, Al2O3 regulates the compactness of the glass network and precisely controls the Li + -Na + / K + The ion exchange rate of ZrO2 and K2O together determine the diffusion channels of molten salt ions, with K2O directly affecting the formation efficiency and uniformity of surface compressive stress. By controlling the relationship within the scope of this application, a perfect balance is achieved between "controllable crystallization in the exposed area" and "suppression of crystallization in the non-exposed area," fundamentally reducing the crystallinity difference between the two areas and avoiding stress concentration and cracking risks caused by excessive height difference after strengthening. Simultaneously, the ion diffusion capacity of the glass network is synergistically controlled, making the ion exchange rates of the exposed and non-exposed areas more consistent. This avoids cracking and edge chipping problems caused by uneven exchange and forms a uniform and sufficiently deep compressive stress layer, achieving an order-of-magnitude improvement in the glass's impact resistance and compressive strength.

[0047] In one embodiment of this application, Z is SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O), where 6≤Z≤9. SiO2, as the main glass network forger, determines the glass's basic forming ability, viscosity, and thermal stability relative to the ratio of various modified oxides and additives. CeO2 is a UV photosensitizer, absorbing UV light and releasing electrons; Ag2O is a nucleating agent, accepting electrons to form Ag colloidal crystal nuclei; Sb2O3 / SnO2 is an electron storage agent, delaying electron recombination and ensuring the uniformity of the photosensitizing reaction; ZrO2 and K2O regulate subsequent crystal phase growth. These components collectively determine the exposure sensitivity and blackening uniformity of the photosensitive glass. Simultaneously, control is implemented from the exposure and crystallization stages: the SiO2 framework restricts the excessive migration of Ag clusters and abnormal grain growth, making the grain size in the exposed area uniform and controllable; at the same time, it avoids the local enrichment of functional components in the non-exposed area, effectively suppressing spontaneous crystallization in the non-exposed area, and fundamentally reducing the property differences between the two areas. This application, through a control formula within the scope of this application, limits the total ratio of framework components to fully photosensitive functional components, avoiding both the problems of crystal nucleus agglomeration and spontaneous crystallization devitrification in the non-exposed area caused by excessive functional components, and the problems of poor photosensitivity response and incomplete blackening caused by insufficient functional components. This achieves uniform grain refinement in the exposed area and precise suppression of crystallization in the non-exposed area, solving the problem of excessive crystallinity in both areas from the source of the photosensitivity reaction, laying a core foundation for the uniformity of subsequent chemical strengthening. The synergistic effect of the relationships (SiO2+Al2O3) / (ZrO2+K2O) and SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O) ensures that the chemically strengthened product possesses excellent surface compressive stress, a reasonable stress layer depth, and overall superior impact and compressive strength. This ensures that while introducing various functional components (nucleating agents, photosensitizers, fluxes, etc.) to achieve specific functions (photosensitivity, microcrystallization), the basic glass-forming ability and structural uniformity are not compromised, laying a solid compositional foundation for the preparation of high-performance photosensitive microcrystalline glass and successful chemical strengthening. Ultimately, this achieves a smaller difference in glass properties between exposed and unexposed areas, resulting in a smaller height difference (Δd2) and a balanced ion exchange effect after chemical strengthening, ultimately endowing the product with high and uniform mechanical strength.

[0048] In one embodiment of this application, the crystallinity of the exposed area is 1.7%-10%, preferably 1.7%-5.8%; the crystallinity of the non-exposed area is 0.4%-3%, preferably 0.4%-2.74%. For example, the crystallinity of the exposed area can be 1.7%, 3.4%, 5.8%, 7.0%, 9%, 10%, or a range of any two values ​​therein; the crystallinity of the non-exposed area can be 0.4%, 1.0%, 2%, 2.74%, 3%, or a range of any two values ​​therein. Within the scope of this application, limiting the crystallinity of the exposed area is beneficial to the light-shielding performance of the exposed area due to the synergistic effect of the lithium metasilicate crystalline phase and Ag nanocrystals. If the crystallinity is too low, the number of crystalline phases is insufficient, resulting in weak scattering and absorption of visible light, making effective blackening impossible. If the crystallinity is too high, the grains tend to agglomerate and coarsen (exceeding 10 nm), leading to decreased light-shielding uniformity and even a mottled phenomenon of "localized over-black / localized light transmission," which may also cause stress concentration within the glass. If the crystallinity in the non-exposed area exceeds 3%, the excessive crystalline phase will lead to enhanced visible light scattering and a significant decrease in transmittance. If the crystallinity in the non-exposed area is too low (below 0.4%), the stability of the glass network structure is insufficient, and ion exchange may become uncontrolled during chemical strengthening, leading to uneven stress. Limiting the crystallinity of the exposed and non-exposed areas within the scope of this application can effectively achieve both light-shielding and light-transmitting functions and improve the stability of the glass network structure, thus laying a good foundation for subsequent strengthening processes.

[0049] In one embodiment of this application, the absolute value of the difference in crystallinity between the exposed region and the unexposed region is 0-6%.

[0050] The second aspect of this application provides a chemically strengthened photosensitive microcrystalline glass, the base glass composition of which includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: <0. 32wt%, X: 0.2%~0.80%, where X is an oxide of Ag. The chemically strengthened photosensitive glass-ceramic includes an exposed region and a non-exposed region. The height difference between the exposed region and the non-exposed region is Δd2, where 40nm≤Δd2≤180nm. The CS of the non-exposed region is 200MPa-350MPa, preferably 280MPa-320MPa. The CS_50 of the non-exposed region is 65MPa-180MPa, preferably 88MPa-110MPa. For example, Δd2 can be 40nm, 70nm, 100nm, 130nm, 150nm, 180nm, or a range of any two values ​​therein. The inventors discovered that excessive height difference leads to noticeable steps on the glass surface, causing stress concentration at these steps upon impact or pressure, directly resulting in cracking. Conversely, insufficient height difference (<40nm) means insufficient crystallinity difference between the two regions, making precise optical zoning of light blocking and transmission impossible. Limiting Δd2 within the scope of this application ensures the crystallinity difference between the exposed and non-exposed areas, achieving the core functions of light blocking and transmission, while avoiding stress concentration caused by excessive steps, thus resolving the contradiction between optical function and mechanical properties. This application, through designing the composition of the base glass, can control an appropriate ion exchange rate, reducing the crystallinity difference between the exposed and non-exposed areas, thereby reducing the height difference Δd2 between the exposed and non-exposed areas after chemical strengthening within the scope of this application. This reduces the difference in the relative loss rate of glass mass during the strengthening process, ultimately achieving high impact resistance and high compressive strength in chemically strengthened photosensitive microcrystalline glass. CS is the surface compressive stress; for example, the CS of the non-exposed area can be 200MPa, 280MPa, 300MPa, 320MPa, 350MPa, or any range of two values. Within the scope of this application, limiting the CS (compressive stress) of the non-exposed area helps balance "damage resistance" and "stress safety threshold." This effectively resists the propagation of surface defects caused by external impacts and friction, while avoiding spontaneous breakage and degradation of light transmittance due to excessive stress. This ensures that the non-exposed area possesses sufficient mechanical protection capabilities while maintaining its core function of high light transmittance. CS_50 is the compressive stress at a depth of 50 μm from the glass surface. For example, the CS_50 of the non-exposed area can be 65 MPa, 88 MPa, 110 MPa, 120 MPa, 150 MPa, 180 MPa, or any range of two values.Within the scope of this application, the CS_50 limiting the non-exposed area facilitates the construction of a dual-layer stress protection system for the product's surface and depth. This not only resists surface damage but also effectively blocks crack propagation, significantly improving the product's fracture resistance. CS and CS_50 within the scope of this application ensure suitable glass strength, and the height difference within the scope of this application reduces the occurrence of cracks and edge chipping defects due to inconsistent shrinkage between the exposed and non-exposed areas during strengthening. Both factors jointly determine the mechanical properties of the glass, resulting in a chemically strengthened photosensitive microcrystalline glass with high impact resistance and high compressive strength.

[0051] The inventors discovered that SiO2, a glass-forming oxide, forms an irregular, continuous network of silicon-oxygen tetrahedral structural units, constituting the framework of glass. Increasing the SiO2 content raises the glass's heat treatment temperature (Tg), enhancing thermal stability and helping to suppress phase separation during heat treatment, thus reducing the light absorption coefficient of heat-treated glass. However, excessive SiO2 content leads to high viscosity and a high melting temperature. Conversely, decreasing the SiO2 content lowers the melting temperature and suppresses component volatilization during melting, but insufficient SiO2 content makes heat treatment more prone to phase separation, resulting in an increased light absorption coefficient and a lower Tg, thus reducing thermal stability.

[0052] Al₂O₃ is a glass network intermediate, with [AlO₄] as the base. 5- Tetrahedrons enter the glass network structure. Al₂O₃ acts as a crystallization inhibitor; under sufficient free oxygen conditions, Al₂O₃… 3+ It enters the glass network in a tetrahedral form due to [AlO4]. 5- The charge number is relatively higher than that of [SiO4]. 4- An additional negative charge will attract a Li. + It is close to the compensated electricity price. An increase in Al2O3 can raise the Tg temperature of glass, enhance its thermal stability, and help suppress phase separation during the glass heat treatment process, reducing the light absorption coefficient of the exposed heat-treated glass. However, too much Al2O3 will raise the melting temperature of the glass.

[0053] The main crystalline phase precipitated in photosensitive glass is lithium metasilicate. The introduction of Li₂O is to ensure the precipitation of this crystalline phase and also acts as a flux. When the Li₂O content is less than 8.0%, there is insufficient favorable Li₂O content in the glass network during chemical strengthening. + This is not conducive to Li + -Na + Exchange reduces strength; when the Li2O content is greater than 12%, the unirradiated area of ​​the glass is prone to crystallization during heat treatment, affecting the transmittance of the transparent area and increasing the crystallinity, which is not conducive to improving strength.

[0054] Na₂O and K₂O are external components of the glass network and act as fluxes, lowering the glass's melting temperature.+ K + In the case of existence, Na + K + The lithium will preferentially enter the aluminum-silicon-oxygen network to compensate for the electricity price, which to some extent maintains the lithium content in the lithium-rich region, making the Si / Li ratio in the lithium-rich region closer to the chemical ratio of Li₂SiO₃. This results in the precipitated crystalline phase of the photosensitive glass containing Na₂O and K₂O being lithium metasilicate. However, excessive Na₂O and K₂O can lead to phase separation and turbidity during the glass heat treatment process, increasing the light absorption coefficient and lowering the Tg temperature, thus worsening thermal stability.

[0055] ZrO2 can increase the crystal content of glass and refine the grain size. If the ZrO2 content is too low, it will not act as a nucleating agent, while if the content is too high, it will easily deposit during high-temperature melting, affecting the crystallization performance of photosensitive glass materials.

[0056] Sb₂O₃ is a weak reducing agent and also acts as a clarifying agent. 3+ Ce is preferentially reduced during the glass melting process. 4+ Maintain Ce 3+ The effective content of Sb2O3 is limited to 0.3wt%~0.7wt%.

[0057] CeO2 is a photosensitizer. During glass melting, it is reduced by Sb2O3 to form Ce2O3. Ce2O3 is excited by ultraviolet light and transforms into Ag. + The CeO2 content is insufficient to provide electrons. When the CeO2 content is below 0.05 wt%, it cannot provide enough electrons, resulting in an excessively low crystal content, excessively high transmittance and insufficient blackness in the irradiated glass area. When the CeO2 content is above 0.4 wt%, although it can provide more electrons, if it leads to an overly stable glass structure, it will restrict the migration and nucleation of Ag clusters, causing coarsening of silver particles, weakening photosensitivity, and affecting the precision of subsequent micro-pattern etching. In addition, since Ce2O3 has a significant ultraviolet absorption peak at 312 nm, excessive CeO3 content will reduce the transmittance of ultraviolet light to the glass.

[0058] In one embodiment of this application, the drop ball impact energy of the chemically strengthened photosensitive microcrystalline glass is 0.30J-0.48J. For example, the drop ball impact energy of the chemically strengthened photosensitive microcrystalline glass can be 0.30J, 0.35J, 0.4J, 0.48J, or a range of any two of these values. Limiting the drop ball impact energy of the chemically strengthened photosensitive microcrystalline glass to the range of this application is beneficial for comprehensively ensuring the impact resistance of the glass under different usage scenarios, from everyday drops to severe impacts, thereby reducing the repair rate of end products.

[0059] In one embodiment of this application, the static compressive strength of the chemically strengthened photosensitive glass-ceramic is 300N-400N. For example, the static compressive strength of the chemically strengthened photosensitive glass-ceramic can be 300N, 330N, 350N, 370N, 400N, or a range of any two of these values. Limiting the static compressive strength of the chemically strengthened photosensitive glass-ceramic to the range specified in this application is beneficial for improving the compressive strength of the product.

[0060] In one embodiment of this application, the drop height of the chemically strengthened photosensitive microcrystalline glass is 50cm-75cm. For example, the drop height of the chemically strengthened photosensitive microcrystalline glass can be 50cm, 60cm, 70cm, 75cm, or a range of any two of these values. Limiting the drop height of the chemically strengthened photosensitive microcrystalline glass to the range specified in this application is beneficial for improving the impact resistance of the product.

[0061] The third aspect of this application provides a method for preparing the photosensitive microcrystalline glass of the first aspect of this application, the method comprising:

[0062] (1) Prepare raw materials according to the composition, mix, melt, shape and anneal the raw materials to obtain base glass;

[0063] (2) The base glass is processed to obtain a glass substrate sheet;

[0064] (3) Divide the glass substrate sheet into a first region and a second region, mask the first region, and do not mask the second region to obtain the masked substrate glass.

[0065] (4) The masked substrate glass is subjected to radiation treatment to obtain the irradiated substrate glass; the first region of the irradiated substrate glass is the non-exposed region, and the second region of the irradiated substrate glass is the exposed region.

[0066] (5) Heat-treat the irradiated substrate glass to obtain photosensitive microcrystalline glass.

[0067] In one embodiment of this application, the heat treatment includes nucleation and crystallization. The nucleation temperature is 450℃-500℃, and the nucleation time is 210min-250min. The crystallization heating rate is 1℃ / min-10℃ / min, and the crystallization temperature is 595℃-610℃. The crystallization time is 30min-47min. The nucleation treatment mainly aims to uniformly disperse the Ag colloid and control the formation of crystal nuclei, providing nucleation sites for subsequent crystallization. The crystallization process promotes the growth of Li2SiO3 around the Ag nuclei, forming a composite structure of microcrystalline and glassy phases. This process controls crystal growth by controlling the crystallization temperature and time, achieving a smaller difference in crystallinity between the exposed and unexposed areas, thereby improving the photosensitive properties and machinability of the glass.

[0068] In this application, melting includes: melting raw materials at 1450℃~1500℃; the forming methods include, but are not limited to, float glass, overflow, calendering and casting.

[0069] In this application, the processing includes one or more of the following: shaping, cutting, CNC machining, grinding and polishing, cleaning, 3D hot bending, and sweeping.

[0070] In one embodiment of this application, the radiation treatment includes: ultraviolet light irradiation for 5-10 minutes, the wavelength of the ultraviolet light irradiation being 300nm-320nm, and the intensity of the ultraviolet light irradiation being 89mw / cm². 2 -260mw / cm 2 .

[0071] In this application, radiation treatment includes single-sided radiation treatment or double-sided radiation treatment.

[0072] The fourth aspect of this application provides a method for preparing chemically strengthened photosensitive microcrystalline glass, comprising a two-step chemical strengthening treatment of the photosensitive microcrystalline glass described in the first aspect. The two-step chemical strengthening treatment includes: a first-step chemical strengthening: placing the photosensitive microcrystalline glass in a salt bath containing 0wt%-40wt% KNO3, 60wt%-100wt% NaNO3, and 0wt%-0.03wt% LiNO3; the first-step chemical strengthening temperature is 360℃-400℃; and the first-step chemical strengthening time is 20min-50min. A second-step chemical strengthening: placing the photosensitive microcrystalline glass after the first-step chemical strengthening in a salt bath containing 0wt%-10wt% NaNO3 and 90wt%-100wt% KNO3; the second-step chemical strengthening temperature is 365℃-405℃; and the second-step chemical strengthening time is 10min-25min. During the strengthening process, a small amount of Li, excluding the crystalline phase, is present in the exposed region. + and Na from the salt bath + Exchange, a large amount of Li in the non-exposed region besides the crystalline phase + and Na from the salt bath + The exchange process leads to a discrepancy between the exchange amounts in the exposed and unexposed areas, with the exchange amount in the unexposed areas being greater than that in the exposed areas. Increasing the chemical strengthening temperature can accelerate the ion diffusion rate (consistent with the Arrhenius relation), but when the temperature exceeds a certain point, the glass network structure begins to undergo thermal relaxation and micro-deformation, triggering the following negative effects: Stress relaxation effect: At high temperatures, the ability of atoms to rearrange within the glass is enhanced, and the already formed surface compressive stress layer is gradually released, weakening the strengthening effect brought about by ion exchange; Increased reverse diffusion: K +At high temperatures, stress not only diffuses into the glass interior but also more easily escapes from the surface into the molten salt, causing "exchange backflow" and reducing the net exchange capacity. When the strengthening time is too high, the overall exchange capacity between the non-exposed and exposed areas exceeds 0.3%, forming a step greater than 180nm (height difference), which leads to excessively high surface compressive stress, triggering microcracks and actually reducing the mechanical strength of the glass. Furthermore, prolonged strengthening damages the internal network structure of the glass, resulting in a decrease in strength. When the strengthening time is too low, the glass surface cannot form a sufficient compressive stress layer, leading to a decrease in strength; while the internal tensile stress is not fully released, making it prone to crack propagation under stress, reducing the glass's impact resistance.

[0073] In this application, the thickness of the glass substrate sheet is 0.4mm-5mm.

[0074] In one embodiment of this application, the photosensitive glass-ceramic is processed before chemical strengthening.

[0075] The fifth aspect of this application provides the application of the photosensitive microcrystalline glass described in the first aspect or the chemically strengthened photosensitive microcrystalline glass described in the second aspect in smart wearable devices, mobile terminals, camera modules or vehicle components.

[0076] Example

[0077] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.

[0078] Test methods and equipment:

[0079] X-ray diffraction (XRD) test:

[0080] The X-ray diffractometer used in this application is a Shimadzu XRD-6100, with copper as the target material. Kα radiation was used with a copper target for testing, with 2θ = 10°~50°, a scanning speed of 6° / min, an operating voltage of 40kV, and an operating current of 30mA. The XRD diffraction data were analyzed using Jade software (JADE Standard 8.6) to determine the crystalline phase in the sample.

[0081] Crystallinity (or crystal content): The crystallinity of the chemically strengthened photosensitive glass-ceramic sample can be obtained by importing the XRD test results (RAW format) into the Rietveld X-ray diffraction data refinement software Jade for fitting and calculation. Specifically, the ratio of the fitted crystal phase peak area to the fitted total peak area is the crystallinity of the chemically strengthened photosensitive glass-ceramic.

[0082] CS and CS_50 tests:

[0083] The CS and CS_50 of the glass were tested using a scattered light photoelastic stress meter (model SLP-2000, light source 518nm).

[0084] Before using the SLP2000 to test the stress of the glass under test, the instrument parameters need to be set. Click the Meas Cnd (C) option on the main page, set the refractive index (n=1.54), sample thickness, and photoelastic coefficient value (B=25.5) before conducting the test.

[0085] Drop ball test:

[0086] A sample with a diameter of 28.5 × 0.78 mm is placed on a glass support fixture, and a 64 g steel ball is dropped from a specified height. The maximum drop height that the sample can withstand without breaking is defined as the drop height. Specifically, the drop height is tested starting at 120 mm, with the ball landing three times at the center of the chemically strengthened photosensitive microcrystalline glass. Without breakage, the height is then increased by 20 mm each time, successively increasing to 80 mm, 100 mm, 120 mm, 140 mm, 160 mm, 180 mm, 200 mm, 220 mm, 240 mm, 260 mm, 280 mm, 300 mm, 320 mm, 340 mm, and above.

[0087] The impact energy calculation formula is E = mgh, where E is the impact energy (unit: J), m is the mass of the steel ball (unit: kg), h is the height of the bottom of the steel ball from the sample (unit: m), and g is the gravitational acceleration (9.8 m / s²).

[0088] Single-unit static pressure strength test:

[0089] Place the φ28.5×0.78mm glass sample on the bottom ring of the tensile testing machine (LT-850A). Start the testing software and set the moving speed of the compression rod (rod diameter 20mm, ball head diameter 20mm) to 10mm / min. Click "Start Test." The compression rod will apply force to the center of the glass sample at the set moving speed until the glass cracks and breaks. The testing software will automatically read the force (N) at the time of glass breakage as the test result. Take 10 glass samples in the same condition for testing, and take the average value of the test results as the single-rod static compressive strength of the glass sample.

[0090] Height difference test:

[0091] The height difference between the exposed and unexposed areas before chemical strengthening is Δd1, and the height difference between the exposed and unexposed areas after chemical strengthening is Δd2. First, the φ28.5×0.78mm sample to be tested is placed in the fixture of a white light interferometer (Banshi Intelligent Technology (Shenzhen) Co., Ltd., AM-7000). Ensure the sample surface is flat and clean, avoiding oil stains or scratches that could affect measurement accuracy. Start the interferometer for measurement. The scanning range is typically set to 10–20 μm based on the sample roughness. The sampling interval must satisfy Nyquist's theorem (e.g., λ / 8, approximately 70 nm). Record interference fringes or spectral information. The system automatically focuses to ensure initial focal plane positioning and monitors the interference fringe contrast in real time (maintaining it above 80%) to ensure signal quality. The acquired interference fringes are processed using algorithms such as Fourier transform to extract phase information. Data repeatability is verified through multiple measurements (error is typically less than 0.5%). Finally, the thickness value and uniformity analysis report are output.

[0092] Example 1

[0093] Preparation of substrate glass:

[0094] According to the weight percentage of each oxide in Table 1, prepare each raw material with a total mass of 2000g. Then mix them in a V-type mixer for 30 minutes to obtain a uniformly mixed raw material. Melt the uniformly mixed raw material in a platinum crucible at 1450℃, stir and clarify, then draw and shape it, and finally anneal it to obtain a glass substrate.

[0095] Preparation of glass sheets:

[0096] After cutting, shaping and polishing the obtained glass substrate, a glass substrate sheet with dimensions of 50mm (length) × 50mm (width) × 1.25mm (thickness) is obtained.

[0097] Preparation of photosensitive microcrystalline glass:

[0098] The obtained glass substrate sheet is divided into a first region and a second region. Both opposing main surfaces of the first region are coated with anti-UV ink for masking, while the second region is not masked, resulting in a double-sided masked substrate glass with the same structure. The two main surfaces of the double-sided masked substrate glass with the same structure are then subjected to irradiation treatment. First, one surface is irradiated: under parallel ultraviolet light with a wavelength of 310 nm, the intensity of the ultraviolet irradiation treatment is 130 mw / cm². 2The glass was irradiated on one side for 5 minutes, and then the other side was irradiated under the same conditions. After ultraviolet irradiation, the glass was nucleated at 460℃ for 210 minutes and then crystallized at 600℃ for 38 minutes to obtain a photosensitive microcrystalline glass with colored exposed areas and transparent unexposed areas. After polishing, a photosensitive microcrystalline glass with a thickness of 0.78 mm was obtained.

[0099] Preparation of chemically strengthened glass-ceramics:

[0100] The photosensitive microcrystalline glass sheet with dimensions of 50mm (length) × 50mm (width) × 0.78mm (thickness) obtained above was subjected to the first step of chemical strengthening: treatment in a mixed nitrate salt bath of 70wt% NaNO3 + 30wt% KNO3 + 0.03wt% LiNO3 (here referring to the total amount of NaNO3 and KNO3 in the mixed molten salt, which contains 0.03wt% LiNO3) at 370℃ for 40min; then the second step of chemical strengthening was carried out: treatment in a mixed nitrate salt bath of 1wt% NaNO3 + 99wt% KNO3 at 390℃ for 15min; a chemically strengthened photosensitive microcrystalline glass with a thickness of 0.78mm was obtained.

[0101] Examples 2 to 18, Comparative Examples 1 to 31

[0102] Except for adjusting the weighing of each raw material according to the weight percentage of each oxide in Table 1 and adjusting the process parameters according to Table 2, the rest is the same as in Example 1.

[0103] Comparative Examples 1-1 to 1-10

[0104] The photosensitive microcrystalline glass obtained in Example 12 was subjected to a two-step chemical strengthening treatment. The chemical strengthening process parameters are shown in Table 2.

[0105] The experimental data for each embodiment and comparative example are shown in Table 3. In Table 3, " / " indicates that it does not exist.

[0106] Table 1

[0107] Table 2

[0108] Note: In the table, 70Na30K0.03Li refers to the total amount of NaNO3 and KNO3 in the mixed molten salt, which contains 70wt% NaNO3 + 30wt% KNO3. 3+ 0.03 wt% LiNO3; 80Na20K0.03Li refers to a mixed molten salt containing 80 wt% NaNO3 and 20 wt% KNO3. 3+0.03 wt% LiNO3; 90Na10K0.03Li refers to a mixed molten salt containing 90 wt% NaNO3 and 10 wt% KNO3. 3+ 0.03 wt% LiNO3; 60Na40K0.03Li refers to a mixed molten salt containing 60 wt% NaNO3 and 40 wt% KNO3. 3+ 0.03wt% LiNO3; 70Na30K0.03Li refers to a mixed molten salt containing 70wt% NaNO3 and 30wt% KNO3. 3+ 0.03 wt% LiNO3; 99K1Na means the mixed molten salt contains 99 wt% KNO3 + 1 wt% NaNO3; 90K10Na means the mixed molten salt contains 90 wt% KNO3 + 10 wt% NaNO3; 100K means the mixed molten salt contains 100 wt% KNO3.

[0109] Table 3

[0110] As can be seen from Tables 1 to 3, the chemical composition of the photosensitive microcrystalline glass is within the scope of this application, and the height difference Δd1 between the exposed and unexposed areas of the photosensitive microcrystalline glass is controlled within the scope of this application. The resulting photosensitive microcrystalline glass has good impact resistance, which lays a solid foundation for the preparation of high-performance photosensitive microcrystalline glass and the acquisition of high-performance chemically strengthened photosensitive microcrystalline glass.

[0111] As can be seen from Comparative Examples 1 to 10, although the chemical composition of the photosensitive microcrystalline glass is within the scope of this application, the height difference Δd1 between the exposed area and the non-exposed area is too large, which inevitably results in poor impact resistance of the obtained photosensitive microcrystalline glass. The height difference Δd2 of the chemically strengthened photosensitive microcrystalline glass obtained after subsequent chemical strengthening is too large, which leads to low monomer static pressure, drop ball height, and drop ball impact energy of the chemically strengthened photosensitive microcrystalline glass, indicating that its compressive strength and impact resistance are poor.

[0112] As can be seen from Comparative Examples 11 to 29, the chemical composition of the photosensitive microcrystalline glass is outside the scope of this application, Δd1 is too large, and the height difference Δd2 of the chemically strengthened photosensitive microcrystalline glass obtained by subsequent chemical strengthening treatment is too large, which in turn leads to the monomer static pressure, drop ball height and drop ball impact energy of the chemically strengthened photosensitive microcrystalline glass being too low.

[0113] As can be seen from Comparative Examples 30 and 31, the components do not conform to the range of the formula of this application, Δd1 is not within the range of this application, Δd2 of the chemically strengthened photosensitive microcrystalline glass is too large, and the monomer static pressure and drop ball height of the obtained chemically strengthened photosensitive microcrystalline glass are too small, indicating that its compressive strength and impact resistance are poor.

[0114] As can be seen from Tables 1 to 3, the chemical composition and height difference Δd2 of the chemically strengthened photosensitive microcrystalline glass of this application are within the scope of this application, and the CS of the non-exposed area and the CS_50 of the non-exposed area are within the scope of this application. The chemically strengthened photosensitive microcrystalline glass has higher monomer static pressure, drop ball height and drop ball impact energy, indicating that it has higher compressive strength and impact resistance.

[0115] This application also provides a method for preparing photosensitive microcrystalline glass. As can be seen from Examples 1 to 18, the photosensitive microcrystalline glass prepared according to the preparation method of this application has a composition within the scope of this application, with a small height difference Δd1 between the exposed area and the non-exposed area, thereby having high impact resistance. This lays a good foundation for the high performance of subsequent chemically strengthened photosensitive microcrystalline glass. After chemical strengthening, chemically strengthened photosensitive microcrystalline glass with good compressive strength and impact resistance can be obtained.

[0116] The preparation methods of Comparative Examples 1-10 are not within the scope of this application. The height difference Δd1 between the exposed and unexposed areas of the obtained photosensitive microcrystalline glass is too large. Therefore, it is impossible to obtain photosensitive microcrystalline glass with good compressive strength and impact resistance. The compressive strength and impact resistance of the photosensitive microcrystalline glass after subsequent chemical strengthening are also relatively poor.

[0117] This application also provides a method for preparing chemically strengthened photosensitive microcrystalline glass. The chemical strengthening process parameters of Comparative Examples 1-1 to 1-10 are not within the scope of this application, and the resulting chemically strengthened photosensitive microcrystalline glass has poor compressive strength and impact resistance.

[0118] Furthermore, XRD analysis shows that the crystal phase in both the exposed and non-exposed areas of the chemically strengthened photosensitive glass in this embodiment is Li₂SiO₃. The diffraction peaks in both areas are relatively uniform with no significant differences, indicating that the crystal phase in the exposed and non-exposed areas of the chemically strengthened photosensitive glass in this embodiment is consistent and the grain size difference is small. In contrast, the crystal phase in both the exposed and non-exposed areas of the chemically strengthened photosensitive glass in the comparative example is also Li₂SiO₃, but the heights of the diffraction peaks in the exposed area are significantly higher than the corresponding diffraction peaks in the non-exposed area, indicating a significant difference in crystal phase size and crystallinity between the exposed and non-exposed areas. The inventors believe that this may lead to density differences between the exposed and non-exposed areas, resulting in different exchange rates during the strengthening process. Figure 1 As an example, the XRD pattern of the chemically strengthened microcrystalline glass of Example 1 of this application is provided; Figure 2 The XRD pattern of the chemically strengthened glass-ceramic of Comparative Example 9 is presented.

[0119] In this application, "the peak heights of the LiSiO3 characteristic diffraction peaks corresponding to the exposed area and the unexposed area are close to each other" means: (Referring to...) Figure 1 and Figure 2 Unlike Comparative Example 9 Figure 2 In the case shown, the height of the characteristic diffraction peak of LiSiO3 in the exposed area is significantly higher than that in the unexposed area. However, in the chemically strengthened photosensitive glass-ceramic of this application, there is no significant intensity difference between the characteristic diffraction peaks of LiSiO3 in the exposed and unexposed areas.

[0120] In this application, the main crystalline phase of both the exposed and non-exposed regions of the chemically strengthened photosensitive microcrystalline glass is LiSiO3. The peak heights of the characteristic diffraction peaks of LiSiO3 in both regions are close to each other, reflecting that the difference in grain size between the exposed and non-exposed regions is small. This reduces the density difference between the exposed and non-exposed regions, weakens the difference in ion exchange rate during the chemical strengthening process, reduces the height difference after strengthening, and improves the impact and compressive strength of the glass.

[0121] The height difference between the exposed and unexposed areas of the photosensitive microcrystalline glass in this embodiment before and after chemical strengthening is significantly smaller than that of the photosensitive microcrystalline glass in the comparative embodiment before and after chemical strengthening. Therefore, the photosensitive microcrystalline glass in this application has better compressive strength and impact resistance before and after strengthening.

[0122] For example, Figure 3a and Figure 4a The figures show the height difference between the exposed and unexposed areas before and after chemical strengthening in Embodiment 10 of this application, respectively, using white light interference color fringe patterns. As can be seen from the figures, the height difference increases after chemical strengthening.

[0123] Figure 3b and Figure 4b The figures shown are white light interference curves illustrating the height difference between the exposed and unexposed areas before and after enhancement in Embodiment 10 of this application. It can be seen that the height difference before enhancement is 32.9 nm, and the height difference after enhancement is 42.0 nm.

[0124] Figure 5a and Figure 6a The figures show the height difference between the exposed and unexposed areas of Comparative Example 9 of this application before and after enhancement, respectively, using white light interference color fringes. It can be seen from the figures that the height difference increases after chemical enhancement.

[0125] Figure 5b and Figure 6b The figures shown are white light interference curves illustrating the height difference between the exposed and unexposed areas of Comparative Example 9 of this application before and after enhancement. It can be seen that the height difference before enhancement is 160.0 nm, and the height difference after enhancement is 575.0 nm.

[0126] In this application, both the white light interference color fringe pattern and the corresponding white light interference curve are visualizations of the height difference, and they convey the same meaning. Figure 3a and Figure 3b The meanings are the same. With Figure 3a and Figure 3b Taking this as an example, the white light interference color fringe pattern and white light interference curve of this application will be explained in detail. Figure 3a The left side shows the height difference of the test area, and the right side shows the height color scale. Figure 3a The surface height distribution data is extracted by connecting the two dots in the middle. Figure 3b , Figure 3b The distance between "0" and "1" is 510 μm, and the corresponding height difference is 32.9 nm.

[0127] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. A photosensitive microcrystalline glass, characterized in that, The basic glass composition includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: 0wt%~0.32wt%, X: 0.2wt%~0.80wt%, where X is an oxide of Ag; the photosensitive microcrystalline glass includes an exposed area and a non-exposed area; the height difference between the exposed area and the non-exposed area is Δd1, where 30nm≤Δd1≤62nm.

2. The photosensitive microcrystalline glass according to claim 1, characterized in that, Y is (SiO2+Al2O3) / (ZrO2+K2O), 7≤Y≤11.

3. The photosensitive microcrystalline glass according to claim 1 or 2, characterized in that, Z is SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O), 6≤Z≤9.

4. The photosensitive microcrystalline glass according to claim 1, characterized in that, The crystallinity of the exposed area is 1.7%-10%, preferably 1.7%-5.8%; the crystallinity of the unexposed area is 0.4%-3%, preferably 0.4%-2.74%.

5. The photosensitive microcrystalline glass according to claim 1, characterized in that, The absolute value of the difference in crystallinity between the exposed area and the unexposed area is 0-6%.

6. A chemically strengthened photosensitive microcrystalline glass, characterized in that, The basic glass composition includes: SiO2: 65wt%~74wt%, Al2O3: 5wt%~9wt%, Li2O: 8wt%~12wt%, Na2O: 1wt%~3wt%, K2O: 2wt%~4wt%, ZrO2: 4wt%~7wt%, CeO2: 0.05wt%~0.32wt%, Sb2O3: 0.3wt%~0.7wt%, SnO2: 0wt%~0.32wt%, and X: 0.2wt%~0.80wt%, where X is an oxide of Ag. The chemically strengthened photosensitive microcrystalline glass includes exposed and non-exposed areas. The height difference between the exposed region and the non-exposed region is Δd2, where 40nm ≤ Δd2 ≤ 180nm; the CS of the non-exposed region is 200MPa-350MPa, preferably 280MPa-320MPa; the CS_50 of the non-exposed region is 65MPa-180MPa, preferably 88MPa-110MPa; the main crystal phase of both the exposed region and the non-exposed region is LiSiO3. XRD testing of the chemically strengthened photosensitive glass-ceramic is performed using copper target Kα rays, with 2θ ranging from 10° to 50°. The peak heights of the characteristic diffraction peaks of LiSiO3 corresponding to the exposed region and the non-exposed region are close to each other.

7. The chemically strengthened photosensitive microcrystalline glass according to claim 6, characterized in that, Y is (SiO2+Al2O3) / (ZrO2+K2O), 7≤Y≤11.

8. The chemically strengthened photosensitive glass crystal according to claim 6 or 7, characterized in that, Z is SiO2 / (ZrO2+K2O+Sb2O3+SnO2+CeO2+Ag2O), 6≤Z≤9.

9. The chemically strengthened photosensitive glass crystal according to claim 6, characterized in that, The falling ball impact energy of the chemically strengthened photosensitive microcrystalline glass is 0.30J-0.48J.

10. The chemically strengthened photosensitive glass crystal according to claim 6, characterized in that, The static compressive strength of the chemically strengthened photosensitive microcrystalline glass is 300N-400N.

11. The chemically strengthened photosensitive glass crystal according to claim 6, characterized in that, The drop height of the chemically strengthened photosensitive microcrystalline glass is 50cm-75cm.

12. A method for preparing photosensitive microcrystalline glass according to any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Prepare raw materials according to the composition, mix, melt, shape and anneal the raw materials to obtain base glass; (2) The base glass is processed to obtain a glass substrate sheet; (3) Divide the glass substrate sheet into a first region and a second region, perform masking treatment on the first region, and do not perform masking treatment on the second region to obtain the masked substrate glass; (4) The masked substrate glass is subjected to radiation treatment to obtain irradiated substrate glass; The first region of the irradiated substrate glass is a non-exposed region, and the second region of the irradiated substrate glass is an exposed region. (5) The irradiated substrate glass is heat-treated to obtain photosensitive microcrystalline glass.

13. The method for preparing photosensitive microcrystalline glass according to claim 12, characterized in that, The heat treatment includes nucleation and crystallization; the temperature of the nucleation is 450℃-500℃, and the time of the nucleation is 210min-250min; the heating rate of the crystallization is 1℃ / min-10℃ / min, the temperature of the crystallization is 595℃-610℃, and the time of the crystallization is 30min-47min.

14. The method for preparing photosensitive microcrystalline glass according to claim 12, characterized in that, The masking process includes masking using double-sided ink printing or double-sided masking, and the first region has an optical density >5 at wavelengths of 380nm-780nm after the masking process.

15. The method for preparing photosensitive microcrystalline glass according to claim 12, characterized in that, The radiation treatment includes: ultraviolet light irradiation for 5-10 minutes, wherein the wavelength of the ultraviolet light irradiation is 300nm-320nm, and the intensity of the ultraviolet light irradiation is 89mw / cm². 2 -260mw / cm 2 .

16. A method for preparing chemically strengthened photosensitive microcrystalline glass, characterized in that, This includes subjecting the photosensitive microcrystalline glass according to any one of claims 1-5 to a two-step chemical strengthening treatment, wherein the two-step chemical strengthening treatment includes: First step chemical strengthening: The photosensitive microcrystalline glass is placed in a salt bath in a mixed nitrate solution containing 0wt%-40wt% KNO3, 60wt%-100wt% NaNO3 and 0wt%-0.03wt% LiNO3. The temperature of the first step chemical strengthening is 360℃-400℃ and the time of the first step chemical strengthening is 20min-50min. The second step of chemical strengthening: The photosensitive microcrystalline glass after the first step of chemical strengthening is placed in a salt bath in a mixed nitrate containing 0wt%-10wt% NaNO3 and 90wt%-100wt% KNO3. The temperature of the second step of chemical strengthening is 365℃-405℃, and the time of the second step of chemical strengthening is 10min-25min.

17. The application of the photosensitive microcrystalline glass according to any one of claims 1 to 5 or the chemically strengthened photosensitive microcrystalline glass according to any one of claims 6 to 11 in smart wearable devices, mobile terminals, camera modules or vehicle components.